2006
DOI: 10.1007/s10831-006-9000-2
|View full text |Cite
|
Sign up to set email alerts
|

The prosodic structure and pitch accent of Northern Kyungsang Korean

Abstract: This study investigates the underlying tonal pattern of pitch accent, tone interaction, focus effects, and the prosodic structure of Northern Kyungsang Korean (NKK) by examining tone-syllable alignment and the realization of pitch accent in different tonal/prosodic contexts. Based on quantitative data, we propose that the underlying tone of pitch accent is H*+L and that the left edge of a prosodic word is marked by a low boundary tone (%L). Our observation, with respect to the tone interaction of different lex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 5 publications
1
44
0
Order By: Relevance
“…Chen's (2006) study of the durational correlates of focus in Mandarin showed that focus domains are marked by longer durations at their edges than their non-focused counterparts. And focusmarking in Japanese and Korean also appears to involve optional boundary marking: the initial boundaries of focused constituents can block lexical pitch accent downstep in the same way that intonational phrase-boundaries do (for Japanese: Pierrehumbert and Beckman 1988;Venditti, Maekawa and Beckman 2008; but see Kubozono 2006;for Korean: Jun 1993;Jun et al 2006;Kenstowicz andSohn 1997, Kim 1997). Japanese speakers can also insert a prosodic boundary tone at the end of the focused constituent to set it of from a following constituent; this type of boundary insertion is often found when the focused word is utterance-initial (Venditti et al 2008).…”
Section: Durational Mechanisms For Signaling Word Boundaries In Promimentioning
confidence: 99%
“…Chen's (2006) study of the durational correlates of focus in Mandarin showed that focus domains are marked by longer durations at their edges than their non-focused counterparts. And focusmarking in Japanese and Korean also appears to involve optional boundary marking: the initial boundaries of focused constituents can block lexical pitch accent downstep in the same way that intonational phrase-boundaries do (for Japanese: Pierrehumbert and Beckman 1988;Venditti, Maekawa and Beckman 2008; but see Kubozono 2006;for Korean: Jun 1993;Jun et al 2006;Kenstowicz andSohn 1997, Kim 1997). Japanese speakers can also insert a prosodic boundary tone at the end of the focused constituent to set it of from a following constituent; this type of boundary insertion is often found when the focused word is utterance-initial (Venditti et al 2008).…”
Section: Durational Mechanisms For Signaling Word Boundaries In Promimentioning
confidence: 99%
“…North Kyungsang Korean is spoken using a lexical pitch accent in the southeast area of Korea. Previous studies on North Kyungsang Korean have traditionally demonstrated that high and low tones are associated with syllables, reflecting a phonologically approached theory (Chung, 1991;Jun et al, 2006;Kenstowicz & Sohn, 1997;Kim, 1976;Kim, 1988;Kim, 1997). Recently, Kim (2012Kim ( , 2015Kim ( , 2018 has researched the lexical pitch accent in North Kyungsang Korean using an imitation task with the data of children and adults.…”
Section: Introductionmentioning
confidence: 96%
“…This study investigates the imitation patterns of adults and children speaking North Kyungsang Korean by measuring log-produced f0 (fundamental frequency) intervals. Previous studies have suggested that North Kyungsang Korean has a lexical pitch accent (Chung, 1991;Jun et al, 2006;Kenstowicz & Sohn, 1997;Kim, 1976;Kim, 1988;Kim, 1997). For example, [kaci] is produced as HL 'kind', LH 'eggplant', and HH 'branch'.…”
Section: Introductionmentioning
confidence: 97%
“…The previous studies on North Kyungsang Korean (Kim, 1976;Kim, 1988;Chung, 1991;Kim, 1997;Kenstowicz & Sohn, 1997;Jun et al, 2006) have suggested that the pitch accent of this dialect in Korean is lexically determined (e.g., [kaci]: HL 'kind,' LH 'eggplant,' HH 'branch'). The current paper deals with how the length in syllables (for two-and three-syllable words) is related to fundamental frequency (f0) intervals.…”
Section: Introductionmentioning
confidence: 99%
“…The lexical pitch accent in North Kyungsang Korean has traditionally been examined from the point of view of the association between tone and syllable relative to phonological interpretation (Kim, 1976;Kim, 1988;Chung, 1991;Kim, 1997;Kenstowicz & Sohn, 1997;Jun et al, 2006). The acquisition of lexical pitch accent in Korean has not received any attention from researchers.…”
Section: Introductionmentioning
confidence: 99%